Slower Is Higher: Threshold Modulation of Cortical Activity in Voluntary Control of Breathing Initiation - Pouget, Pierre; Allard, Etienne; Poitou, Tymothée; Raux, Mathieu; Wattiez, Nicolas; Similowski, Thomas (Frontiers in Neuroscience, 2018)
Speech or programmed sentences must often be interrupted in order to listen to and interact with interlocutors. Among many processes that produce such complex acts, the brain must precisely adjust breathing to produce adequate phonation. The mechanism of these adjustments is multifactorial and still poorly understood. In order to selectively examine the adjustment in breath control, we recorded respiratory-related premotor cortical potentials from the scalp of human subjects while they performed a single breathing initiation or inhibition task. We found that voluntary breathing is initiated if, and only if, the cortical premotor potential activity reaches a threshold activation level. The stochastic variability in the threshold correlates to the distribution of initiation times of breathing. The data also fitted a computerized interactive race model. Modeling results confirm that this model is also as effective in respiratory modality, as it has been found to be for eye and hand movements. No modifications were required to account for respiratory cycle inhibition processes. In this overly simplified task, we showed a link between voluntary initiation and control of breathing and activity in a fronto-median region of the cerebral cortex. These results shed light on some of the physiological constraints involved in the complex mechanisms of respiration, phonation, and language.